A laboratory model for evaluating relapse of undesirable caregiver behavior. Issue 2 (20th July 2018) - Mitteer, Daniel R.; Greer, Brian D.; Fisher, Wayne W.; Briggs, Adam M.; Wacker, David P.
Abstract : The success of behavioral treatments like functional communication training depends on their continued implementation outside of the clinical context, where failures in caregiver treatment adherence can lead to the relapse of destructive behavior. In the present study, we developed a laboratory model for evaluating the relapse of undesirable caregiver behavior that simulates two common sources of disruption (i.e., changes in context and in treatment efficacy) believed to affect caregiver treatment adherence using simulated confederate destructive behavior. In Phase 1, the caregiver's delivery of reinforcers for destructive behavior terminated confederate destructive behavior in a home‐like context. In Phase 2, the caregiver implemented functional communication training in a clinical context in which providing reinforcers for destructive or alternative behavior terminated confederate destructive behavior. In Phase 3, the caregiver returned to the home‐like context, and caregiver behavior produced no effect on confederate destructive or alternative behavior, simulating an inconsolable child. Undesirable caregiver behavior relapsed in three of four treatment‐adherence challenges.